Optimization of the magnetic system of a vacuum-arc plasma source with a straight line filter - Aksyonov, D.S.; Vasyliev, V.V.; Luchaninov, A.A.; Strelnitskij, V.E. (Вопросы атомной науки и техники, 2021)
The vacuum-arc plasma source with a rectilinear filter has been optimized for deposition of coatings on large size products. The calculations of the magnetic configuration options of the system were performed by using the FEMM program. New design of the output coil of the filter allows increase by 1.3 times the efficiency of plasma transportation to the substrate with a diameter of 300 mm. Plasma instabilities are proposed for the explanation the features of the motion of vacuum-arc plasma through the regions of an inhomogeneous magnetic field in a rectilinear macroparticles filter with a “magnetic island”.